Thermometry at the nanoscale using lanthanide-containing organic-inorganic hybrid materials - Brites, C. D. S.
Non-invasive accurate thermometers with high spatial resolution and operating at sub-micron scales, where the conventional methods are ineffective, is currently a very active field of research strongly stimulated in the last couple of years by the challenging demands of nanotechnology and biomedicine. Here we report on the temperature operation range, spatial resolution and long-term stability of Eu3+/Tb3+ luminescent thermometers involving magnetic hybrid nanoparticles and di-ureasil thin films. (c) 2011 Elsevier B.V. All rights reserved.